Myoepithelioma of parotid gland: a case report - Lemos, Ricardo Costa S.; Fonseca, Rui (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Myoepithelioma (ME) is a benign tumor, arising predominantly from major and minor salivary glands (SG). Clinically, it presents as a painless mass with a slow growth. In our case report, this lesion occurred in a 51-year-old man, and presented as a well-defined oval mass on the right parotid region. The magnetic resonance imaging study confirmed the presence of a lesion with benign features that was excised surgically by partial superficial parotidectomy. The histopathological and immunohistochemical analysis confirmed the diagnosis of parotid ME. Other SG tumors such as pleomorphic adenoma are differential diagnoses of ME. Complete surgical excision reduces the rate of recurrence.